Influences on treatment-seeking and antibiotic use for common illnesses in eastern China - Tingting Zhang; Hanyi Lin; Xinping Zhao; Wei Wang; Fei Yan; Helen Lambert (BMC, 2023)
Abstract Background Antibiotic resistance rates remain high in China where antibiotics are widely used for common illnesses. This study aimed to investigate the influences on people's decisions on treatment and antibiotic use for common illnesses in eastern China. Methods Semi-structured interviews were conducted with 29 patients recruited through convenience sampling between July 2020 and January 2021 in one hospital in County A in Zhejiang Province, and one hospital and one village clinic in County B in Jiangsu Province, respectively. All interviews were audio-recorded, transcribed verbatim and thematically analysed. This study is nested in a larger interdisciplinary mixed method project and we also compared our qualitative findings with quantitative results from a household survey conducted as part of this wider project. Results Participants' decisions about treatment-seeking and antibiotic use for common illnesses were found to be influenced by four interactive domains. (i) Self-evaluation of illness severity: Participants tend to self-treat minor conditions with ordinary medicines first and do not resort to antibiotics unless the condition worsens or is considered inflammation- related. Visiting healthcare facilities is seen as the final option. (ii) Access to and trust in care: These treatment-seeking practices are also associated with the perception, in contrast with retail pharmacies, hospitals provide professional and trustworthy care but are difficult to access, and hence require visiting only for severe illness. (iii) Prior experience: previous medical treatment and experiences of self-medication also influence participants' treatment decisions including the use of antibiotics. (iv) Medication characteristics: Participants view antibiotics as powerful medicines with harms and risks, requiring consumers to carefully trade off benefits and harms before use. Conclusions People's treatment decisions in relation to antibiotic use in eastern China are influenced by an interplay of lay conceptual models of illnesses and antibiotics and broader organisational, social, and contextual factors. Interventions focusing on individual education to incorporate biomedical knowledge into lay understandings, and reducing situational and social incentives for self-medicating with antibiotics by strengthening access to quality professional care, would be helpful in promoting antibiotic stewardship.